Regulatory T cells and transplantation tolerance. (July 2013) - Hilbrands, Robert; Howie, Duncan; Cobbold, Stephen; Waldmann, Herman
The success of clinical organ transplantation relies on life-long use of immunosuppressive drugs that target immune responses associated with graft rejection. Preclinical studies in mice have convincingly demonstrated that robust, long-term transplantation tolerance can be achieved after a short-term treatment with T-cell coreceptor and costimulation blockade even for a fully mismatched graft. Such therapeutically induced tolerance requires the induction of Foxp3 + Tregs, which are essential for both the development and maintenance of the tolerant state. Recent advances in understanding the molecular and epigenetic mechanisms underlying the induction and stabilization of Foxp3 expression, thus guiding Foxp3 + Treg differentiation, have revealed novel therapeutic targets in animal models that can be translated to harness Foxp3 + Tregs from within the patient. Such in vivo induced Foxp3 + Tregs can also induce the tolerant state. Pharmacological compounds are available to exploit these targets and their further development holds great promise for clinical translation.